Pemberdayaan Kelompok Tani Ternak Desa Sendangdalem melalui Pelatihan Pembuatan Silase dan Pupuk Organik Padat - Barokah, Umi; Zaida Muflih , Ghufron; Prasetyo, Prasetyo; Dwi Chalisty, Vian; Minannurrokhman, Minannurrokhman; Tri Wibowo, Ferdiansyah; Janah, Roihatul; Nurbaeti, Wiwit; Fauzan, Afdhal (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
Sendangdalem Village is a village in Padureso District, Kebumen Regency, where the majority of the population earns a living as farmers and livestock breeders. The natural resources it possesses have great potential for economic development, particularly in the livestock sector. KTT Sidomaju has not yet optimally managed its livestock business, such as providing green fodder with a cut and curry system, requiring daily forage searches due to a lack of feed stocks and livestock waste that is simply piled up due to not being properly managed. The cut and carry feeding method makes livestock time inefficient. Unprocessed livestock waste can produce a pungent odor and has no economic value. The purpose of this community service activity is to increase knowledge and skills related to silage feed management and processing solid livestock waste into solid organik fertilizer through composting technology. The Community Service activity began with a survey and observation, socialization, counseling, and the production of silage feed and solid organik fertilizer. The community service activity in Sendangdalem Village received a positive response from the community and KTT Sido Maju. Silage feed processing can provide continuous feed and save time. Processing sheep manure into solid organik fertilizer can reduce environmental pollution and speed up the process of decomposing the material into compost that is ready to be used for plants.